2006
DOI: 10.1080/02699200400026900
|View full text |Cite
|
Sign up to set email alerts
|

An atypical case of Foreign Accent Syndrome

Abstract: A new case of Foreign Accent Syndrome is described. This American woman presented with a British- or Australian- sounding accent after stroke, which resulted in a lacunar infarct in the left internal capsule. The atypical etiology and apparent changes in lexical use are described. It is hypothesized that an abnormally tense vocal tract posture may account for phonetic changes in vowel quality and a higher average fundamental frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 11 publications
1
21
1
3
Order By: Relevance
“…Rather, this vowel substitution pattern was limited to her 'yah' productions in spontaneous speech. Unlike previous cases of lexical substitution reported in patients with FAS (Laures-Gore et al, 2006;Ryalls & Whiteside, 2006), the patient was aware of these modifications and was able to exert conscious control to repair the 'yah' to a 'yeah', when pressed. Given the phonetic and semantic similarity of the two utterances, it is unlikely this is a form of circumlocution.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Rather, this vowel substitution pattern was limited to her 'yah' productions in spontaneous speech. Unlike previous cases of lexical substitution reported in patients with FAS (Laures-Gore et al, 2006;Ryalls & Whiteside, 2006), the patient was aware of these modifications and was able to exert conscious control to repair the 'yah' to a 'yeah', when pressed. Given the phonetic and semantic similarity of the two utterances, it is unlikely this is a form of circumlocution.…”
Section: Discussioncontrasting
confidence: 62%
“…In the patient they analysed, explanations (b) and (c) were considered plausible accounts of the consonantal fortitions and lowered incidence of vowel weakening processes observed. Tense vocal tract settings have been viewed as possible explanations in a number of recent studies of FAS Moen, 2000;Ryalls & Whiteside, 2006). An alternative basis for FAS was advanced by Blumstein et al (1987) who suggested that both segmental and prosodic effects in their patient may be explained by a general prosodic disturbance-a disturbance in speech timing (see also Blumstein & Kurowski, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, her foreign accent was accompanied by codeswitching, with occasional French words and grammatical errors typical of native French speakers. Similar features have been reported in a handful of cases (e.g., Gurd et al, 2001;Reeves & Norton, 2001;Roth, Fink, Cherney, & Hall, 1997;Ryalls & Whiteside, 2006;Seliger, Abrams, & Horton, 1992). In contrast, our patient's speech profile, like the majority of FAS cases, was generically foreign in nature, unrelated to previous accent exposure, and restricted to pronunciation changes.…”
Section: Discussionsupporting
confidence: 61%
“…Reported changes in intonation include a variety of -sometimes contradictory -features: a higher mean pitch (e.g. Blumstein et al, 1987;Coelho & Robb, 2001;Ryalls & Whiteside, 2006); inappropriately large and sharp pitch excursions on prominent syllables (e.g. Avila, González, Parcet & Belloch, 2004;Moonis et al, 1996); exaggerated terminal falls (Ingram et al, 1992;Moen, 2006); reduced pitch range (GraffRadford et al, 1986;Kanjee, Watter, Sévigny & Humphreys, 2010;Verhoeven & Mariën, 2010); and the inappropriate use of intonation to indicate statements (i.e.…”
Section: Introductionmentioning
confidence: 99%